Growth Allocation Shifts in the Invasive Hydrilla verticillata Under Interspecific Competition with Native Submerged Macrophytes - Letícia da Costa; Luíz Alberto Vieira; Thaísa Sala Michelan; Alvaro Herrera Vale; Wagner Antonio Chiba de Castro (Plants)
Communities with high native species diversity tend to be less susceptible to the establishment of invasive species, especially in studies that test their local impact. This study investigated the impact of competition between native submerged aquatic macrophytes (SAMs) (Egeria najas and Egeria densa) and the exotic Hydrilla verticillata, recognized for its invasive potential in aquatic ecosystems, through a mesocosm experiment conducted over six months. Two treatments were evaluated: the intraspecific competition of H. verticillata and an interspecific competition involving all three species. The plants were cultivated under controlled conditions, with the foliar and subterranean biomass being monitored to analyze resource allocation patterns. The results showed that, under interspecific competition, the mean foliar biomass of H. verticillata was significantly higher compared to the intraspecific treatment, while the subterranean biomass was reduced in the presence of native species. We conclude that native species alter the biomass allocation pattern of the invader, favoring foliar structures over subterranean ones. Among the mechanisms of invasiveness, differential resource allocation represents an important strategy for the adaptation and competitiveness of invasive species influenced by environmental factors and resource competition. These findings contribute to the understanding of competitive interactions in aquatic ecosystems and have implications for the management and control of invasive species, highlighting the importance of promoting native diversity to mitigate invasibility. Future studies should investigate the impacts of reduced subterranean structures on the persistence and spread of submerged invasive species.